Role of intestinal mucin-2 in the effectiveness of the treatment of Helicobacter spp. infection in laboratory mice - E. A. Litvinova; M. D. Belyaev; A. V. Prokhortchouk; V. S. Korostina; E. B. Prokhortchouk; E. N. Kozhevnikova (Вавиловский журнал генетики и селекции)
Abnormal synthesis of the main intestinal proteoglycan mucin-2 is typical of ulcerative colitis and Crohn’s disease in humans. Those morphological changes of the mucus layer affect the diversity of the intestinal microflora. Antibiotics may be ineffective or even dangerous to humans or animals deficient for mucin-2 because of the risk of sepsis and chronic inflammation. In this study, we investigated the potential of antibiotics (clarithromycin, amoxicillin, and metronidazole) in elimination of pathogenic infection from Muc2 knockout mice (Muc2–/–). We assayed the population sizes of pathogens (Helicobacter spp.) and symbiotic (E. coli) bacteria in the intestines of animals as a criterion of antibiotic efficacy. The damaging effect of antibacterial treatment on the host body was estimated from their survival rate. Three antibiotics were ineffective in the elimination of Helicobacter spp. from mucin-2-deficient mice. Moreover, the mortality of Muc2 knockout mice during the antibacterial treatment was 60 %. The survival of wild-type mice (C57BL/6J) during the treatment was 100 %. The weight of wild-type mice showed no decrease during the treatment. The Helicobacter spp. pathogen was fully eradicated from wild-type mice. Thus, therapy of Helicobacter spp. infection in mucin-2 deficient animals is not only poorly efficient but even deadly. The high susceptibility to antibiotics allows Muc2 knockout mice to be used as a test model to evaluate the pharmacological safety of new antibiotics.